2018
DOI: 10.1590/1984-0462/;2018;36;2;00011
|View full text |Cite|
|
Sign up to set email alerts
|

Aulas De Educação Física E Desfechos Relacionados À Saúde Em Estudantes Brasileiros

Abstract: Objective: To analyze the association between participation and physical activity during Physical Education classes with health outcomes in Brazilian students.Methods: 681 Brazilian students (50.5% female) aged 10 to 17 years participated in this cross-sectional study. Independent variables analyzed were participation and physical activity during Physical Education classes, both assessed using a self-report questionnaire. The outcomes were: cardiorespiratory fitness (20-meter Shuttle Run test), muscle strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
7
0
5
Order By: Relevance
“…However, comparisons between our results and those from the available scientific literature should be performed with caution, since the outcomes analyzed in our study were the self-reported frequencies of specific forms of physical activity and SB, while other studies analyzed objective measurements of time spent in moderate to vigorous physical activity (MVPA) [ 4 6 , 22 , 26 ] or self-reported measures in order to assess compliance with the recommendation of 60 min daily of MVPA [ 7 9 , 12 , 21 , 23 26 ]. In our study, we used a health surveillance tool, the purpose of which is to qualitatively assess the forms of physical and sedentary activities and provide a description of the total frequency of activities reported on the previous day, as a proxy for the physical activity level of the participants[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, comparisons between our results and those from the available scientific literature should be performed with caution, since the outcomes analyzed in our study were the self-reported frequencies of specific forms of physical activity and SB, while other studies analyzed objective measurements of time spent in moderate to vigorous physical activity (MVPA) [ 4 6 , 22 , 26 ] or self-reported measures in order to assess compliance with the recommendation of 60 min daily of MVPA [ 7 9 , 12 , 21 , 23 26 ]. In our study, we used a health surveillance tool, the purpose of which is to qualitatively assess the forms of physical and sedentary activities and provide a description of the total frequency of activities reported on the previous day, as a proxy for the physical activity level of the participants[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisa com adolescentes de escolas públicas do Brasil mostrou que os estudantes mais ativos durante as aulas apresentaram maior probabilidade de atingir os critérios de saúde para a aptidão cardiorrespiratória e a força muscular. No entanto, as aulas não protegeram os alunos de sobrepeso, obesidade ou pressão alta, pois foram de 50 minutos duas vezes por semana, volume inferior ao necessário para cumprir com a meta recomendada para essa faixa etária (23).…”
Section: Discussionunclassified
“…It has been suggested that PE classes may play a significant role in CRF development [ 7 9 ] and monitoring [ 10 ], as there are a number of field tests available that allow whole school classes to be assessed in one session [ 11 , 12 ]. Therefore, PE teachers have several quality tools to assess the students’ CRF.…”
Section: Introductionmentioning
confidence: 99%
“…Although the school setting and PE classes offer a platform that might help for improving [ 7 , 8 ] and monitoring [ 10 ] of CRF, recent studies suggest that in the last decades CRF appears to have declined in children and adolescents worldwide [ 16 , 17 ]. Due to its importance, this evidence is of great concern.…”
Section: Introductionmentioning
confidence: 99%